Regeneration and characterization of spent bleaching earth: recycling in the corn oil bleaching process - Ikhlas Benkhoud; Lassaad Ben Mansour (Journal of Environmental Engineering and Landscape Management)
The spent bleaching earth (SBE) is a solid waste from the edible oil refining industry which generates soil contamination was successfully recycled after deoiling through an extraction process using different organic solvents, followed by heat treatment. In the current study, the effects of factors, such as solvent to (SBE) ratio [1:1–5:1], temperature [20–40 °C], and stirring time [30–60 min] on the efficiency of extracted oil were investigated by maceration method. Characterization analyses (SEM, XRD, XRFA and TGA) were carried out to compare the characteristics of samples. The best oil extraction efficiency was obtained at the highest level of solvent to (SBE) ratio (MR = 5) at 30 °C temperature and at the 45 minutes stirring time this condition led to 72.82% oil extraction yield. The corn oil bleaching efficiency using the SBE treated at optimal condition and heated at 400 °C was improved to 84.75%.